Aplikasi Bisnis Syirkah D’durian Park, Wonosalam, Jombang, Jawa Timur - Krisnaningsih, Diah; Masruchin, Masruchin; Fauji, Imam (ITB AAS INDONESIA Surakarta, 2023)
The COVID-19 pandemic and measures to prevent its spread caused a severe contraction in the world economy. The International Monetary Fund projects that the global economy will shrink by around 4.4 percent in 2020, the worst recession since the Second World War. Indonesia's gross domestic product is certain to experience a contraction of 1.1 percent in 2020 - a drastic drop from the projected pre-pandemic growth of 5.3 percent, causing a loss of jobs and income for the wider community. Microeconomic growth must be encouraged to grow faster for small to national scale economic recovery. The concept of syirkah as a discourse for Islamic business solutions to accelerate economic growth is very appropriate, especially in Indonesia with natural wealth in 38 provinces and abundant human resources + 357 million people. D'durian Park, Wonosalam, Jombang is one of the leading agribusinesses with the sirkah mukhabarah system in Wonosalam, Jombang with the main business units namely the Agrotourism Garden Plot (KKA) and agrotourism with the main commodity being Indonesia's superior durian and was founded in November 2019. Methods This research, namely qualitative case study, aims to describe, describe, explain, explain about the implementation of a theory in a particular field, such as the application of the syirkah mukhabarah business theory run by D'Durian Park Wonosalam, Jombang.